The inconvenient Lonnie Johnson : blues, race, identity - Simon, Julia, 1961- (American music history., 2022)
"Lonnie Johnson is a blues legend. His viruosity on the blues guitar is second to none, and his influence on artists from T-Bone Walker and B. B. King to Eric Clapton is well established. A master of multiple instruments, Johnson recorded with jazz icons such as Duke Ellington and Louis Armstrong and played vaudeville music, ballads, and popular songs. The Inconvenient Lonnie Johnson reassesses Johnson's musical legacy, complicating basic assumptions about the blues, its production, and its reception. Julia Simon presents detailed analyses of Johnson's music - his lyrics, technique, and styles - with particular attention to its sociohistorical context. What she reveals is a musician who was able to cross generic, stylistic, and other boundaries almost effortlessly, displaying astonishing adaptability across a corpus of music produced over six decades. Simon introduces us to a musical innovator and a performer keenly aware of his audience and the social categories of race, class, and gender that conditioned the music of his time. Lonnie Johnson's music challenges us to think about not only what we recognize and value in "the blues" but also what we leave unexamined, cannot account for, or choose not to hear." --